Introduction and prospects of use of Allium L. species in North Prychernomor'ya (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
In the article, the prognosis of the practical use of Allium L. species in the North Prychernomor'ya is done on the basis of adaptation abilities in relation to basic limiting ecological factors together with phytochemical, food and ornamental importance. Recommendations onto growing of Allium taken from natural flora are offered.
Keywords: Allium, ecological plasticity, introduction.